Wood plastic composites made with thermally modified birch wood residues. (1st October 2016) - Kuka, E.; Cirule, D.; Kajaks, J.; Andersone, I.; Andersons, B.
Abstract : Thermally modified (TM) wood production has significantly increased in the last decade. The trend for TM wood residues should be similar – rapidly increasing, which has prompted this research on the possible efficient uses of these residues, such as sawdust. One of the possibilities could be the production of wood plastic composites (WPCs). In this work, three different hydrothermal modification regimes were used to modify birch boards. Modified and unmodified birch boards were milled to obtain sawdust. WPCs were made with a two-roll mill, and they consisted of 50 wt-% wood fibres + 50 wt-% polypropylene. Melt flow index (MFI), flexural properties, impact strength, microhardness water absorption and dimensional stability were tested. WPCs with TM wood showed improvement in flexural properties, MFI and other properties, however there was a decrease in impact strength. Scanning electron microscopy pictures of impact strength samples fracture surfaces were taken.